PENGELOLAAN HARTA ZAKAT PERSPEKTIF HUKUM DAN DAMPAKNYA PADA SOSIO-EKONOMI MASYARAKAT (Studi pada Lembaga Amil Zakat Masjid dan Musholla Se-Bandar Lampung) - AS, Susiadi; Putra, Andi Eka (ASAS, 2020)
Management of zakat in Indonesia has two types of institutions, namely the Amil Zakat Agency (BAZ) and the Amil Zakat Institution (LAZ). By definition, the Zakat Management Institution (LPZ) is an institution tasked with managing zakat, infaq, and shadaqah, both formed by the government such as BAZ, as well as those formed by the public and protected by the government such as LAZ. That "Management of zakat is the planning, implementation and coordination activities in the collection, distribution and utilization of zakat." The Amil Zakat Institution (LAZ) is a zakat management institution that was fully formed on the initiative of the people engaged in the field of da'wah, education, social and welfare of Muslims. To maximize the role and function of zakat management institutions, of course, they must be managed as well as possible, they must be accountable, that is, trustworthiness given by muzakki and also trust in distributing it to mustahiq, in the sense of being right on target and effective, including Amil Zakat Institutions managed by all mosques and mushallas in Bandar Lampung. Keywords: zakat, law, socio-economy Pengelolaan zakat di Indonesia terdapat dua jenis Lembaga, yaitu Badan Amil Zakat (BAZ) dan Lembaga Amil Zakat (LAZ). Secara defenitif, Lembaga pengelola zakat (LPZ) merupakan sebuah institusi yang bertugas dalam pengelolaan zakat, infaq, dan shadaqah, baik yang dibentuk oleh pemerintah seperti BAZ, maupun yang dibentuk oleh masyarakat dan dilindungi oleh pemerintah seperti LAZ. Bahwa ”Pengelolaan zakat adalah kegiatan perencanaan, pelaksanaan, dan peng-koordinasian dalam pegumpulan, pendistribusian, dan pendayagunaan zakat.” Lembaga Amil Zakat (LAZ) adalah institusi pengelola zakat yang sepenuhnya dibentuk atas prakarsa masyarakat yang bergerak dalam bidang dakwah, pendidikan, sosial dan kemaslahatan umat Islam. Untuk memaksimalkan peran dan fungsi lembaga pengelolaan zakat, tentunya harus dikelola sebaik mungkin, harus akuntabel, yaitu amanah terhdap kepercayaan yang diberikan oleh muzakki dan juga amanah dalam mendistribusikannya kepada mustahiq,dalam arti tepat sasaran dan tepat guna, termasuk Lembaga-Lembaga Amil Zakat yang dikelola oleh seluruh masjid dan mushalla di Bandar Lampung.Keywords: zakat, hukum, sosio-ekonomi